Hybrid Machining Processes Perspectives on Machining and Finishing - Gupta, Kapil; Jain, Neelesh K.; Laubscher, R. F. (Manufacturing and Surface Engineering, 2016)
This book describes various hybrid machining and finishing processes. It gives a critical review of the past work based on them as well as the current trends and research directions. For each hybrid machining process presented, the authors list the method of material removal, machining system, process variables and applications. This book provides a deep understanding of the need, application and mechanism of hybrid machining processes.